Chromosomal Rearrangements and Origin of the Multiple XX/XY1Y2 Sex Chromosome System in Harttia Species (Siluriformes: Loricariidae) - Deon, Geize Aparecida; Glugoski, Larissa; Sassi, Francisco de Menezes Cavalcante; Hatanaka, Terumi; Nogaroto, Viviane; Bertollo, Luiz Antônio Carlos; Liehr, Thomas; Al-Rikabi, Ahmed; Moreira-Filho, Orlando; Cioffi, Marcelo de Bello; Vicari, Marcelo Ricardo (Frontiers in Genetics, 2022)
The Neotropical Harttia genus comprises species with extensive chromosomal remodeling and distinct sex chromosome systems (SCSs). So far, three different SCSs with male heterogamety have been characterized in the group. In some species, the presence of the XX/XY1Y2 SCS is associated with a decrease in diploid numbers and several chromosomal rearrangements, although a direct relation to sex chromosome differentiation has not been shown yet. Here, we aimed to investigate the differentiation processes that have led to the establishment of the rare XX/XY1Y2 SCS and track its evolutionary history among other Harttia species. For that, four whole chromosome painting probes derived from chromosome 1 of H. torrenticola (HTO-1), chromosomes 9 and X of H. carvalhoi (HCA-9 and HCA-X), and chromosome X from H. intermontana (HIN-X) were applied in nine Harttia species. Homeologous chromosome blocks were located in Harttia species and demonstrated that Robertsonian (Rb) fusions originated HTO-1, HCA-9, and HCA-X chromosomes, while Rb fissions explain Y1 and Y2sex chromosomes. Specifically, in H. intermontana, HCA-X, HCA-9, and the NOR-bearing chromosome demonstrated that homeologous blocks were used in the HIN-X and metacentric pair 2 origins. Consequently, diploid numbers changed between the studied species. Overall, the data also reinforce the existence of unstable genomic sites promoting chromosomal differentiation and remodeling within the genus Harttia.